All-dielectric free-electron-driven holographic light sources - Clarke, Brendan P. (2019)
It has recently been shown that holographically nanostructured surfaces can be employed to control the wavefront of (predominantly plasmonic) optical-frequency light emission generated by the injection of medium-energy electrons into a gold surface. Here, we apply the concept to manipulation of the spatial distribution of transition radiation emission from high-refractive-index dielectric/semiconductor target materials, finding that concomitant incoherent luminescence emission at the same wavelength is unperturbed by holographic surface-relief structures, thereby deriving a means of discriminating between the two emission components.